Karakteristik Sensori dan Indeks Glikemik Biskuit Berbahan Tepung Sorgum dan Tepung Kacang Merah: Sensory Characteristics and Glycemic Index of Biscuits Made from Sorghum Flour and Red Bean Flour - Atmadja, Taufiq Firdaus Al-Ghifari; A’yunin, Nur Arifah Qurota (Universitas Airlangga, 2025)
Background: Diabetes mellitus is a significant nutritional problem faced by adults. Nutritional therapy is one approach to managing this condition. Functional foods, such as sorghum with a low glycemic index, help regulate blood sugar levels and are safe for diabetics. The combination of sorghum and red bean flour in a biscuit formulation provides a functional alternative for diabetics. Objectives: This study analyzed the sensory characteristics and glycemic index values of sorghum and red bean biscuits. Methods: This study used an experimental design with a completely randomized design (CRD), consisting of 3 treatments and 2 replications. The biscuit formulation ratios of sorghum flour, red bean flour, and wheat flour were F1 (50:30:10), F2 (40:30:20), and F3 (30:30:30). A sensory characteristics test was conducted by 30 panelists, and the data were analyzed using ANOVA and Duncan's Further Test. Furthermore, the selected formulas were analyzed for glycemic index values. Results: The findings revealed that Formula F3, consisting of biscuits with a 30:30:30 ratio of wheat flour, sorghum flour, and red bean flour, was the chosen formula with the highest average sensory characteristics in terms of taste, aroma, texture, and color. The Anova test results showed no significant differences in the characteristics of color (p-value 0.065), aroma (p-value 0.520), taste (p-value 0.896), and texture (p-value 0.067). The selected formula (F3) had a glycemic index value of 9.38. Conclusions: Selected sorghum and red bean biscuits (F3) have low glycemic index levels, so these biscuits are safe for consumption by people with diabetes mellitus.